Implementation of Assistance Program For Micro Enterprises (BPUM) in Central Java - Fiki Dzakiyati; Kismartini .; Retno Sunu Astuti (Program Pascasarjana Universitas Negeri Makassar, 2021)
This study is motivated by the impact of the covid pandemic on micro, small and medium enterprises (UMKM). Closing of markets, closing of malls have significant impact on the ability of micro-entrepreneurs to conduct their business. One of the government's efforts to recover the economy matters and help micro-enterprises is with issue Assistance for micro-enterpreneurs (BPUM) program. 905,328 micro-entrepreneurs in Central Java were recorded to have received that government assistance program. However, the large number of BPUM recipients has not been able to fill the needs of UMKM in Central Java. It can be seen from the large number of requests and complaints for BPUM registration, both those posted through the governor's report channel, email, or other social media. This study aims to analyze and describe the implementation of BPUM program in Central Java and also to analyze and describe the supporting and inhibiting factors based on the Van Meter and Van Horne’s policy implementation model. The type of this study is descriptive method with qualitative research approach. The results of this study showed that the implementation of the program needs to be improved due to the lack of communication and limited resources.Keywords: implementation, micro-entrepreneurs, BPUM, Covid-19 pandemic